2017
DOI: 10.1002/ccr3.860
|View full text |Cite
|
Sign up to set email alerts
|

Crazy paving pattern

Abstract: Key Clinical MessageCrazy paving pattern is the name given to characteristic polygonal pattern of interlobular thickening on computed tomography (CT scan) of the lung, which results from accumulation of collagen, interstitial fluid, cell, or other pathology and may be seen in multiple clinical conditions including metastatic cancer as described in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…GGO's are multiple, round and commonly peripheral [15]. The term "crazy paving" was coined due to the polygonal pattern of interlobular thickening seen on scans [16].…”
Section: Covid-19 Grading Systems Based On Chest Ct-scansmentioning
confidence: 99%
“…GGO's are multiple, round and commonly peripheral [15]. The term "crazy paving" was coined due to the polygonal pattern of interlobular thickening seen on scans [16].…”
Section: Covid-19 Grading Systems Based On Chest Ct-scansmentioning
confidence: 99%
“…Fu et al (2016) reported a rare case of pneumothorax as first manifestation of PTCL [14]. Three case reports exist concerning crazy paving pattern of PTCL with lung involvement [[15], [16], [17]]. Recently, Aqeel et al reported a rare case of acute respiratory failure in the setting of antisynthetase syndrome (ASS) in a patient with PTCL where the chest CT revealed extensive bilateral ground glass opacities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Crazy paving is characterized by GGOs associated with interlobular and intralobular septal thickening (Figure 2 ). These CT findings are non-specific since they can be found in numerous pathologies, such as non-specific alveolar proteinosis, acute respiratory distress syndrome and other interstitial pneumonia[ 17 - 19 ].…”
Section: Crazy Pavingmentioning
confidence: 99%